SIKAP MULTIKULTURAL DALAM MENINGKATKAN PRESTASI BELAJAR EKONOMI SISWA SMA DI KOTA MAGELANG - Ratrining Raras Irawati (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2018)
Multicultural attitudes that are instilled in students as an effort to move or act, or do recognize differences and diversity in one frame of togetherness and equality with a way of life respecting, respecting, sincere, and tolerating cultural diversity that lives in the midst of a multicultural society. Multicultural attitudes are important to implement because if students do not have a good multicultural attitude, these students will be reluctant to ask questions so they will not get a good understanding of the material, their learning achievement will decline. And this can occur in the opposite situation when students with fairly good achievements but lack a multicultural attitude, so the student does not have tolerance and cooperation with classmates. This type of research is causal-associative with an approach quantitative. The study population was XI IPS high school students in the Magelang city which totaled 771 students. A sample of 277 students was taken by cluster stratified random sampling technique. Multicultural attitude data, collected through questionnaires, while learning achievement data are collected through achievement tests. The research data were analyzed using simple linear regression techniques. This study concludes four findings. First, there is a positive influence on multicultural attitudes towards economic learning achievement (t = 2.279 and sig. = 0.023 <0.05)